Breathe Easy : Relieving the Symptoms of Chronic Lung Disease. - Mahler, Donald A. (Chicago : University Press of New England, 2017)
An informative and practical guide to better breathing.
Cover -- Title Page -- Contents -- Preface -- Acknowledgments -- 1 | How to Breathe -- 2 | Second Wind -- 3 | Why Am I Short of Breath? -- 4 | Asthma -- 5 | Chronic Obstructive Pulmonary Disease -- 6 | Correct Inhaler Use -- 7 | Interstitial Lung Disease -- 8 | Will Exercise Help? -- 9 | Other Strategies to Relieve Shortness of Breath -- 10 | Traveling with Oxygen -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Lungs -- Diseases; Electronic books